Gestational Diabetes Mellitus Knowledge Among Women of Reproductive Age in Southern Nigeria: Implications for Diabetes Education. (April 2020) - Ogu, Rosemary N.; Maduka, Omosivie; Agala, Vetty; Alamina, Folusho; Adebiyi, Obelebra; Edewor, Ufuoma; Porbeni, Ibimonye; Abam, Claribel
Background: Diabetes mellitus (DM) has attained the status of an epidemic in slow motion. Gestational DM (GDM) is a subtype of DM, which occurs in pregnancy. As part of a baseline assessment, the knowledge of GDM was determined among women of reproductive age. Methods: The study was a descriptive cross-sectional household survey involving 2, 595 women of reproductive age residing in five local government areas in Southern Nigeria. It employed a multistage sampling technique to collect data using an interviewer administered questionnaire built using Open Data Kit software uploaded on android mobile phones. Results: The response rate was 100%. Mean age was 29.25 ± 7.11 years. The majority (2, 351; 90.6%) had heard about DM but only 991 (38.2%) knew that diabetes can occur for the first time in pregnancy. Only 747 (28.8%), 929 (35.8%), and 790 (30.4%) respondents had good knowledge scores for GDM definition and risk factors, GDM screening diagnosis and treatment, and GDM complications, respectively. Only 681 (26.2%) had good overall knowledge of GDM. The major sources of knowledge of GDM were from friends (49.8%), health workers (34.6%), and mass media (10.4%). Residence in two urban local government areas (adjusted odds ratio [adj OR] = 1.79; 95% confidence interval [CI] = 1.36–2.34 and adj OR = 1.89; 95% CI = 1.37–2.61), being married (adj OR = 1.50; 95% CI = 1.16–1.95), and having been pregnant (adj OR = 2.69; 95% CI = 1.99–3.64) positively predicted good overall knowledge of GDM. Conclusion: These results underscore the need for diabetes information and education activities on a large scale targeted at women of reproductive age and their partners for the prevention and control of GDM.